Removal Of Zinc (Ii) Ions From Industrial Wastewater By Activated Carbon Synthesized From Mangrove (Rhizophora Mangle) - Suntharam, Nanthini Mohana (Universiti Sains Malaysia, 2022)
Water pollution has become one of the major issues in Malaysia, due to the release of industrial wastewater containing heavy metals. A suitable adsorbent is required to overcome this problem. Activated carbon is one the common adsorbent used for adsorption processes. Commercially available activated carbon (CAC) is expensive because it is made from non-renewable resources and require advanced processing methods to be produced. In recent years, production for activated carbon from agricultural products has gained attention for its ability in enhancing adsorption processes. Therefore, this study focuses on the potential use of agricultural wastes that are abundantly available in Malaysia, which is mangrove wood, as the precursor for the preparation of inexpensive adsorbent that can be applied to eliminate Zn (II) ions from industrial wastewater. The preparation conditions of the char through microwave heating were made at various radiation power and time. The optimization of microwave radiation power and time was performed using Response Surface Methodology (RSM). The optimal activated carbon was obtained at 616 W and 4 mins under physical activation with CO2. Apart from that, the adsorption process using the mangrove-based activated carbon was investigated under several conditions. The adsorption of Zn (II) ions was performed in batch system. From the experimental data, the ideal KOH impregnation ratio was at 0.5 with 98.97% of activated carbon yield and zinc (II) ions removal of 84.44%. The surface properties and morphology and functional groups of the prepared adsorbents were examined using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FT-IR) and CHNS Elemental Analyzer. The equilibrium phase during adsorption for all batch experiment was reached within 5 hours. The initial concentration of Zn (II) solutions was studied at different concentrations such as 10, 20, 30, 40 and 50 ppm. Whereas the varying temperatures selected for the experiment were 20, 40 and 60°C. The highest Zn (II) ions removal and adsorption capacity was reached at 10 ppm and 60°C with percentages of 82.70% and 20.4043 mg/g respectively. The Langmuir isotherm model exhibit the best fit for the adsorption carried out. The maximum adsorption capacity using Langmuir isotherm was 27.6243 mg/g. The experimental data was also well fitted with pseudo-second order kinetics with R2 value of 0.9999. Finally, the thermodynamics study proved that the adsorption process is naturally endothermic. The process is spontaneous and faster at higher temperature of 60°C.